ACADEMIC WRITING CHALLENGES FOR ESL LEARNERS (Journal of Universal Science Research, 2023)
The aim of this study is to explore some of the difficulties and challenges that ESL learners experience in academic writing. The study seeks to answer the research question, “What challenges do ESL learners encounter in Academic writing?”, ”What factors can make learners experience challenges?” and “How to deal with these Academic writing challenges?”. The goal is to analyze the data collected from a variety of articles regarding the topic, find relevant references or contradictory viewpoints and come to valid conclusions